2016
DOI: 10.1136/annrheumdis-2016-eular.1952
|View full text |Cite
|
Sign up to set email alerts
|

AB0758 The Relationships between Bone Mineral Density and Radiographic Features of Hand or Knee Osteoarthritis in Older Adults: Data from The Dong-Gu Study

Abstract: ObjectivesThe relationship between osteoarthritis (OA) and osteoporosis has exhibited contradictory features over the past four decades. The aim of this study was to evaluate this relationship using separate analysis of the radiographic features of OA whether various radiographic features of OA were associated differently with bone mineral density (BMD) in the Korean elderly.MethodsData were derived from the Dong-gu cohort; 2,354 subjects were enrolled in the present cross-sectional study. Baseline characteris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…This was also accompanied by a faster BMD loss compared with healthy controls. Conversely, Lee et al (2016) observed that hand and knee OA were negatively associated with the BMDs of the lumbar spine and femoral neck.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…This was also accompanied by a faster BMD loss compared with healthy controls. Conversely, Lee et al (2016) observed that hand and knee OA were negatively associated with the BMDs of the lumbar spine and femoral neck.…”
Section: Discussionmentioning
confidence: 91%
“…DXA provides a reliable evaluation of areal bone density but is incapable of distinguishing between cortical and trabecular bone (the parameter measured and discussed in this article) or take into account changes in the bone size, which may overestimate the resultant BMD, whereas pQCT can provide accurate measurements of true vBMD and can supply isolated measurement of cortical and trabecular bones (Abdin-Mohamed et al, 2009). As such, although radiographic OA of the knee is known to be connected to elevated areal BMD at the hip and spine, the vBMD of tibia was not increased in patients with knee OA (Lee et al, 2016).…”
Section: Discussionmentioning
confidence: 94%